Resistance to gapeworm parasite has both additive and dominant genetic components in house sparrows, with evolutionary consequences for ability to respond to parasite challenge. Issue 20 (15th June 2020) - Lundregan, Sarah L.; Niskanen, Alina K.; Muff, Stefanie; Holand, Håkon; Kvalnes, Thomas; Ringsby, Thor‐Harald; Husby, Arild; Jensen, Henrik
Abstract: Host–parasite relationships are likely to change over the coming decades in response to climate change and increased anthropogenic stressors. Understanding the genetic architecture of parasite resistance will aid prediction of species' responses to intensified parasite challenge. The gapeworm " Syngamus trachea " is prevalent in natural bird populations and causes symptomatic infections ranging from mild to severe. The parasite may affect ecological processes by curtailing bird populations and is important due to its propensity to spread to commercially farmed birds. Our large‐scale data set on an insular house sparrow metapopulation in northern Norway includes information on gapeworm prevalence and infection intensity, allowing assessment of the genetics of parasite resistance in a natural system. To determine whether parasite resistance has a heritable genetic component, we performed variance component analyses using animal models. Resistance to gapeworm had substantial additive genetic and dominance variance, and genome‐wide association studies to identify single nucleotide polymorphisms associated with gapeworm resistance yielded multiple loci linked to immune function. Together with genome partitioning results, this indicates that resistance to gapeworm is under polygenic control in the house sparrow, and probably in other bird species. Hence, our results provide the foundation needed to study any eco‐evolutionary processes related to gapeworm infection, and show that it is necessary to use methods suitable for polygenic and nonadditive genetic effects on the phenotype. Abstract : see also the Perspective by María José Ruiz‐López